(untitled) (Sciences & Technology. A, exactes sciences, 2014)
The photocatalytic degradation of Aspirin (ASP) induced by Fe(III) in homogeneous (ASP-Fe(III)-citrate complex) and heterogeneous phase (ASP-Goethite) was studied in aqueous solution up on irradiation at 365nm and by solar light. A dark investigation of system containing a mixture of aspirin and Fe (III) reveals no interaction in homogeneous phase but in heterogeneous phase, the interaction observed was traduced by aspirin adsorption on Goethite in aqueous solution. Under irradiation, Fe(III)-Citrate complex enhance the photooxidation of ASP; a pseudo-first order kinetic model was employed to discuss the results. Against in heterogeneous phase, kinetics is slower and the process is accelerated at acidic pH. The involvement of HO● radicals has been established because of the influence of tertiobutanol used as a scavenger. The photodegradation of ASP in the mixture ASP-Fe(III)-Cit and ASP-Goethite under solar light was significantly accelerated in comparison with artificial irradiation at 365nm.